2014
DOI: 10.1016/j.neuroimage.2013.05.068
|View full text |Cite
|
Sign up to set email alerts
|

GABA estimation in the brains of children on the autism spectrum: Measurement precision and regional cortical variation

Abstract: 1H-magnetic resonance spectroscopy (1H-MRS) and spectral editing methods, such as MEGA-PRESS, allow researchers to investigate metabolite and neurotransmitter concentrations in-vivo. Here we address the utilization of 1H-MRS for the investigation of GABA concentrations in the ASD brain, in three locations; motor, visual and auditory areas. An initial repeatability study (5 subjects, 5 repeated measures separated by ~ 5 days on average) indicated no significant effect of reference metabolite choice on GABA quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
233
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(264 citation statements)
references
References 65 publications
26
233
5
Order By: Relevance
“…This suggestion is consistent, in part, with the suggestion from Bertone et al (2005) that increased lateral inhibition, which is a corollary of increased GABA, underpins GABA levels in frontal (Harada et al, 2011), auditory (Gaetz et al, 2013;Rojas et al, 2013), and motor cortex (Gaetz et al, 2013). However, no differences in GABA levels were found in lenticular nuclei (Harada et al, 2011) or occipital cortex (Gaetz et al, 2013). In addition, blood-plasma levels of GABA have been shown to be increased in children with autism (Dhossche et al, 2002), suggesting that it is premature to rule out the possibility that GABA levels are increased in autism.…”
Section: Orientation Discrimination and Autistic Traits 12supporting
confidence: 83%
“…This suggestion is consistent, in part, with the suggestion from Bertone et al (2005) that increased lateral inhibition, which is a corollary of increased GABA, underpins GABA levels in frontal (Harada et al, 2011), auditory (Gaetz et al, 2013;Rojas et al, 2013), and motor cortex (Gaetz et al, 2013). However, no differences in GABA levels were found in lenticular nuclei (Harada et al, 2011) or occipital cortex (Gaetz et al, 2013). In addition, blood-plasma levels of GABA have been shown to be increased in children with autism (Dhossche et al, 2002), suggesting that it is premature to rule out the possibility that GABA levels are increased in autism.…”
Section: Orientation Discrimination and Autistic Traits 12supporting
confidence: 83%
“…Existing literature provides conflicting evidence with regards to other sensory modalities. As discussed above, at least some individuals with ASC show enhanced auditory discrimination, indicating increased inhibition in auditory cortex; however MRS studies have found lower GABA levels in auditory cortex in ASC (Gaetz et al 2014;Rojas et al, 2014). …”
Section: Differences (See Dickinson Et Al 2014 For a Full Discussion)mentioning
confidence: 95%
“…fMRI task. We investigated functional connectivity related to spontaneous background activity (Fox et al, 2006;Norman-Haignere et al, 2012) during a spatial working memory task. The task consisted of a display of 11 circles positioned on a circular grid.…”
Section: Methodsmentioning
confidence: 99%